2016
DOI: 10.1519/jsc.0000000000001057
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Ingestion Does Not Improve Maximal Isokinetic Force

Abstract: 1The purpose of this study was to assess maximal isokinetic leg extension force in response to 2 glucose ingestion and to determine whether any performance changes occur in a time-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 25 publications
0
24
1
Order By: Relevance
“…Thus, this study provides novel data suggesting that resistance exercise performance can be enhanced by the consumption of a high-carbohydrate preexercise meal. This finding contrasts the results of the only other study to investigate the isolated effects of pre-exercise carbohydrate/energy intake on resistance exercise performance (8). These disparate results might be explained by the nature of the resistance exercise performed, where different mechanisms are likely to limit performance.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Thus, this study provides novel data suggesting that resistance exercise performance can be enhanced by the consumption of a high-carbohydrate preexercise meal. This finding contrasts the results of the only other study to investigate the isolated effects of pre-exercise carbohydrate/energy intake on resistance exercise performance (8). These disparate results might be explained by the nature of the resistance exercise performed, where different mechanisms are likely to limit performance.…”
Section: Discussioncontrasting
confidence: 90%
“…These disparate results might be explained by the nature of the resistance exercise performed, where different mechanisms are likely to limit performance. Performance in the study by Fairchild et al (8) was measured through 3 maximal efforts on an isokinetic dynamometer, with this performance unlikely to be dependent on muscle glycogen availability. By contrast, the higher volume nature of the exercise used in this study, which represents a more ecologically valid resistance training scenario, is more likely to rely on glycogen as a fuel source (22), potentially explaining the observed results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increases in back squat (approximately 15 %) and bench press (approximately 6 %) performance in this previous study (16) were almost identical to those observed in the present study (approximately 15 % and 4 %, respectively), suggesting these previous findings are also likely to be explained by a placebo effect associated with pre-exercise feeding. Fairchild et al (26) reported similar performance responses in three repetitions of isokinetic knee extension/flexion for up to 90 min after consuming either a 75 g carbohydrate drink or a placebo drink. The failure of carbohydrate to enhance performance when delivered in a placebocontrolled manner in the study of Fairchild et al (26) further supports the theory that a pre-exercise meal/carbohydrate consumption might enhance resistance exercise performance via a placebo effect.…”
Section: Discussionmentioning
confidence: 90%
“…Previous research has mainly focused on the effects of a pre-exercise meal on endurance performance (2,(23)(24)(25) . To our knowledge, only two studies have isolated the effect of a pre-exercise meal on resistance exercise performance (16,26) . Naharudin et al (16) observed that performance in four sets of back squat and four sets of bench press was both greater 2 h after a typical high-carbohydrate breakfast (1•5 g carbohydrate/kg body mass) compared with a water-only breakfast.…”
Section: Discussionmentioning
confidence: 99%